Impact Analysis of Disaster Mitigation, Socio-Cultural Adaptation, and Natural Resources Management on Sustainable Tourism Destination in Borobudur Temple, Yogyakarta - Faisal Umardani Hasibuan; Ilham Akbar Bunyamin; Rival Pahrijal (West Science Social and Humanities Studies, 2024)
This study analyzes the impact of disaster mitigation, socio-cultural adaptation, and natural resource management on sustainable tourism at Borobudur Temple, Yogyakarta, a UNESCO World Heritage site. As tourism grows in culturally and ecologically significant destinations, sustainability practices become essential to preserving heritage and ensuring long-term viability. Using a quantitative approach, this study collected data from 190 respondents and analyzed it through Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results demonstrate that each factor—disaster mitigation, socio-cultural adaptation, and natural resource management—significantly contributes to sustainable tourism, with natural resource management showing the strongest impact. These findings highlight the importance of a comprehensive approach in managing heritage tourism, incorporating disaster preparedness, cultural engagement, and resource stewardship. The study provides practical recommendations for stakeholders to enhance sustainability practices, supporting both cultural preservation and economic growth.